Insect herbivory in a mature Eucalyptus woodland canopy depends on leaf phenology but not CO2 enrichment. Issue 1 (December 2016) - Gherlenda, Andrew; Moore, Ben; Haigh, Anthony; Johnson, Scott; Riegler, Markus
Abstract Background Climate change factors such as elevated atmospheric carbon dioxide concentrations (e[CO2 ]) and altered rainfall patterns can alter leaf composition and phenology. This may subsequently impact insect herbivory. In sclerophyllous forests insects have developed strategies, such as preferentially feeding on new leaf growth, to overcome physical or foliar nitrogen constraints, and this may shift under climate change. Few studies of insect herbivory at elevated [CO2 ] have occurred under field conditions and none on mature evergreen trees in a naturally established forest, yet estimates for leaf area loss due to herbivory are required in order to allow accurate predictions of plant productivity in future climates. Here, we assessed herbivory in the upper canopy of matureEucalyptus tereticornis trees at the nutrient-limitedEucalyptus free-air CO2 enrichment (EucFACE) experiment during the first 19 months of CO2 enrichment. The assessment of herbivory extended over two consecutive spring—summer periods, with a first survey during four months of the [CO2 ] ramp-up phase after which full [CO2 ] operation was maintained, followed by a second survey period from months 13 to 19. Results Throughout the first 2 years of EucFACE, young, expanding leaves sustained significantly greater damage from insect herbivory (between 25 and 32 % leaf area loss) compared to old or fully expanded leaves (less than 2 % leaf area loss). This preference of insect herbivores for young expanding leaves combined with discontinuous production of new foliage, which occurred in response to rainfall, resulted in monthly variations in leaf herbivory. In contrast to the significant effects of rainfall-driven leaf phenology, elevated [CO2 ] had no effect on leaf consumption or preference of insect herbivores for different leaf age classes. Conclusions In the studied nutrient-limited naturalEucalyptus woodland, herbivory contributes to a significant loss of young foliage. Leaf phenology is a significant factor that determines the level of herbivory experienced in this evergreen sclerophyllous woodland system, and may therefore also influence the population dynamics of insect herbivores. Furthermore, leaf phenology appears more strongly impacted by rainfall patterns than by e[CO2 ]. e[CO2 ] responses of herbivores on mature trees may only become apparent after extensive CO2 fumigation periods.